Four-week Nordic hamstring exercise intervention for individuals with ACL reconstruction via hamstrings tendon autograft: feasibility of a pilot randomized controlled trial - Grant E. Norte; Neal R. Glaviano; David A. Sherman; Justin L. Rush; Amanda M. Murray (Pilot and Feasibility Studies)
Abstract Background The Nordic hamstring exercise (NHE) has been widely used among uninjured, athletic populations to mitigate the risk of hamstring injury, yet little is known about its utility as an intervention for individuals who undergo ACL reconstruction with hamstring tendon autograft (ACLR-HT). Understanding the feasibility of NHE as a means of enhancing hamstring function may aid in the development of evidence-based recommendations to guide hamstring recovery. Our aim was to determine the feasibility of conducting a pilot NHE trial among individuals with ACLR-HT. Methods We used a single-blind randomized controlled trial with parallel arms to investigate individuals 18–35 years with primary, unilateral ACLR-HT. Twenty-three participants were randomized to a standardized, 4-week (10 session) progressive NHE intervention (n = 17) or usual care control (n = 6) group at a 3:1 ratio. Those randomized to the control group were eligible to open-enroll in the intervention group at the completion of the original study period. Primary feasibility outcomes included recruitment uptake, protocol adherence, dose goal attainment, and retention. Exercise perceptions and safety were also assessed. Summary statistics were used to descriptively report all findings. Results Two control participants were open-enrolled in the intervention group after completing their original study period (n = 19). All participants (88.5% recruitment uptake) adhered to the exercise protocol (100%) and 18 participants (94.7%) attained the total exercise dosage goal. A 100% retention rate was observed, as all participants (intervention 17 randomized, 2 open-enrolled; control 6) returned for their follow-up assessment. Conclusions A standardized, 4-week progressive NHE protocol is feasible for individuals with ACLR-HT. Positive perceptions of exercise, minimal exercise-related discomfort, and no reported adverse events further support the acceptability of this protocol and the likelihood of successful implementation in future efficacy trials. Trial registration ClinicalTrials.gov, NCT05738200. Registered 2 November 2022—retrospectively registered, https://clinicaltrials.gov/study/NCT05738200 .